Up-regulation of TDAG51 is a dependent factor of LPS-induced RAW264.7 macrophages proliferation and cell cycle progression. (3rd March 2016) - Jiao, Han-Wei; Jia, Xiao-Xiao; Zhao, Tian-Jing; Rong, Hui; Zhang, Jia-Ning; Cheng, Ying; Zhu, Hua-Pei; Xu, Kai-Lian; Guo, Shi-Yu; Shi, Qiao-Yun; Zhang, Hui; Wang, Feng-Yang; et al.
Abstract: Context : As a component of the outer membrane in Gram-negative bacteria, lipopolysaccharide (LPS)-induced proliferation and cell cycle progression of monocytes/macrophages. It has been suggested that the proapoptotic T-cell death-associated gene 51 (TDAG51) might be associated with cell proliferation and cell cycle progression; however, its role in the interaction between LPS and macrophages remains unclear. Objective : We attempted to elucidate the role(s) of TDAG51 played in the interaction between LPS and macrophages. Materials and methods : We investigated TDAG51 expression in RAW264.7 cells stimulated with LPS and examined the effects of RNA interference-mediated TDAG51 down-regulation. We used CCK-8 assay and flow cytometry analysis to evaluate the interaction between TDAG51 and LPS-induced proliferation and cell cycle progression in RAW264.7 cells. Results : Our findings indicate that TDAG51 is up-regulated in LPS-stimulated RAW264.7 cells, the TDAG51 siRNA effectively reduced TDAG51 protein up-regulation following LPS stimulation in RAW264.7 cells, the significant changes of the proliferation and cell cycle progression of RAW264.7 cells in TDAG51 Knockdown RAW264.7 cells treated with LPS were observed. Conclusion : These findings suggested that TDAG51 up-regulation is a dependent event during LPS-mediated proliferation and cell cycle progression, and which increase our understanding of the interaction mechanism between LPS and macrophages.